Geometrization of 3 orbifolds of cyclic type - Boileau Michel; Porti Joan (Paris Societe Mathematique de France, 2001)
This monograph volume gives a complete proof of Thurston,s orbifold theorem in the case where all local isotropy groups are cyclic subgroups.The chapters introduces the notion of cone 3-manifold and state the theorems, the proof of the compactness theore
Keywords: Manifolds(Topology)